Energy Yield Analysis of Bifacial Solar Cells in Northeast Mexico: Comparison Between Vertical and Tilted Configurations - Angel Eduardo Villarreal-Villela; Osvaldo Vigil-Galán; Eugenio Rodríguez González; Jesús Roberto González Castillo; Daniel Jiménez-Olarte; Ana Bertha López-Oyama; Deyanira Del Angel-López (Energies)
Bifacial photovoltaic technology is made up of solar cells with the ability to generate electrical power on both sides of the cell (front and rear), consequently, they generate more energy in the same area compared to conventional or monofacial solar cells. The present work deals with the calculation of the energy yield using bifacial solar cells under the specific environmental conditions of Tampico, Tamaulipas, Mexico. Two configurations were compared: (1) tilted, optimized in height and angle, oriented to the south, and (2) vertically optimized in height, oriented east–west. The results were also compared with a standard monofacial solar cell optimally tilted and oriented south. The experimental data were acquired using a current–voltage (I-V) curve tracer designed for this purpose. This study shows that the vertically optimized bifacial solar cell produces similar electrical power to the conventional monofacial solar cell, with the benefit of maximum production in peak hours (8:30 and 16:30). In contrast, in the case of the inclined bifacial solar cell, about 26% more in the production of electrical power was reached. These results guide similar studies in other places of the Mexican Republic and regions with similar latitudes and climate.